Sarco(endo)plasmic Reticulum Ca2+-ATPase-2 Gene: Structure and Transcriptional Regulation of the Human Gene - Angel Zarain-Herzberg; Georgina Alvarez-Fernandez (The Scientific World Journal)
The sarco(endo)plasmic reticulum Ca2+-ATPases (SERCAs) belong to a family of active calcium transport enzymes encoded by the SERCA1, 2, and 3 genes. In this study, we describe the complete structure of the human SERCA2 gene and its 5’ -regulatory region. The hSERCA2 gene is located in chromosome 12 position q24.1 in Contig NT_009770.8, spans 70 kb, and is organized in 21 exons intervened by 20 introns. The last two exons of the pre-mRNA produce by alternatively splicing the cardiac/slow-twitch muscle-specific SERCA2a isoform and the ubiquitous SERCA2b isoform. The sequence of the proximal 225-bp regulatory region of the SERCA2 genes is 80% G+C-rich and is conserved among human, rabbit, rat, and mouse species. It contains a TATA-like-box, an E-box/USF sequence, a CAAT-box, four Sp1 binding sites, and a thyroid hormone responsive element (TRE). There are two other conserved regulatory regions located between positions -410 to -661 bp and from -919 to -1410 bp. Among the DNA cis-elements present in these two regulatory regions there are potential binding sites for: GATA-4, -5, -6, Nkx-2.5/Csx, OTF-1, USF, MEF-2, SRF, PPAR/RXR, AP-2, and TREs. Upstream from position -1.5 kb, there is no significant homology among the SERCA2 genes cloned. In addition, the human gene has several repeated sequences mainly of the Alu and L2 type located upstream from position -1.7 kb, spanning in a continuous fashion for more than 40 kb. In this study, we report the cloning of 2.4 kb of 5’-regulatory region and demonstrate that the proximal promoter region is sufficient for expression in cardiac myocytes, and the region from -225 to -1232 bp contains regulatory DNA elements which down-regulate the expression of the SERCA2 gene in neonatal cardiomyocytes.